Assessment of postoperative swelling and pain following alveolar ridge preservation with different biomaterials: A randomized controlled trial - Mukesh Kumar; Ram Prasad Sah; Neha Kumari; Rohan Kumar; Monalisha Jha; Rakhi Kumari (Wolters Kluwer Medknow Publications, 2024)
Background: This randomized controlled trial aimed to assess and compare postoperative swelling and pain in patients undergoing alveolar ridge preservation using RidgeMax Pro and AlveoGraft Plus. Methods: A total of 20 patients requiring tooth extraction were enrolled in this study and randomly assigned to two groups: Group A received alveolar ridge preservation with RidgeMax Pro and Group B with AlveoGraft Plus. Postoperative swelling was evaluated by measuring facial dimensions using standardized facial photographs at baseline and at 24, 48, and 72 hours postoperatively. Pain was assessed using a visual analog scale (VAS) at the same time points. Statistical analysis was performed using t-tests and repeated measures ANOVA. Results: Both RidgeMax Pro and AlveoGraft Plus demonstrated effective alveolar ridge preservation without any reported complications. In terms of postoperative swelling, Group A (RidgeMax Pro) exhibited significantly lower facial swelling compared to Group B (AlveoGraft Plus) at all time points (P < 0.05). The mean pain scores on the VAS were consistently lower in Group A than in Group B across the assessment time points (P < 0.05). The trend of reduced swelling and pain in Group A persisted throughout the 72-hour follow-up period. Conclusion: Alveolar ridge preservation with RidgeMax Pro (Trade Name: RidgeMax Pro) resulted in significantly reduced postoperative swelling and pain compared to AlveoGraft Plus (Trade Name: AlveoGraft Plus).